2018
DOI: 10.18520/cs/v115/i10/1884-1892
|View full text |Cite
|
Sign up to set email alerts
|

Automation in Transplanting:A Smart Way of Vegetable Cultivation

Abstract: Vegetable transplanting is a labourious and timeconsuming field operation when performed manually. The semi-automatic vegetable transplanters are cumbersome to operate due to limitations on manual feeding rates of seedlings which vary with respect to work duration and skill of the operator. Automation in the field of vegetable transplanters has provided opportunities for savings in labour and time required for transplanting operation in open field and controlled environmental structures, i.e. shade nets or pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…2.0 km/h beyond which the transplanting e ciency reduces. At this speed, the transplanting e ciency was 90.3 % which is considered very good (Khadatkar et al, 2018). It was observed from the result that transplanting percentage increases with increase in speed of operation and then reduces afterwards, which may be due to the reason that at higher speed the soil covering was not proper.…”
Section: ) Transplanting E Ciencymentioning
confidence: 86%
See 1 more Smart Citation
“…2.0 km/h beyond which the transplanting e ciency reduces. At this speed, the transplanting e ciency was 90.3 % which is considered very good (Khadatkar et al, 2018). It was observed from the result that transplanting percentage increases with increase in speed of operation and then reduces afterwards, which may be due to the reason that at higher speed the soil covering was not proper.…”
Section: ) Transplanting E Ciencymentioning
confidence: 86%
“…The result indicated that missing per cent decreases with increase in speed of operation as well as increase in angle of feed roller. At S3=2.0 km/h speed and A2= 30 0 , the miss planting was 2.1 % which is considered very good [24].…”
Section: (6) Miss Plantingmentioning
confidence: 89%
“…In Malaysia, cabbage is commonly grown from transplants and the activity is laborious, back breaking and time consuming when it is implemented manually. The conventional practice requires labours to bend the body and squat in order to punch a hole on the ground and plant seedlings by pressing down the root ball in the soil with hands (Khadatkar et al, 2018). The existence of plastic mulch for weed control has aggravated the difficulties to the labours to prepare a planting hole on a raised bed.…”
Section: Introductionmentioning
confidence: 99%
“…Cabbage transplanter can be found in the market in two forms; automatic and semiautomatic version. The pedestrian-type transplanter is an example of semiautomatic transplanter as it requires a labour to manually transfer the seedlings into the pot supply while automatic tranplanter can eliminate labour as it can self-pick up the seedling from the production tray into the feeder (Khadatkar et al, 2018, Prasanna, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Planting of vegetable crops is rather laborious operation that is usually done by hands. The use of a planting robot can reduce the labor intensity; it can improve the efficiency of seedling planting due to high accuracy with minimal human help [3]. A robot with a computer vision system distinguishes cultivated plants from weeds.…”
Section: Introductionmentioning
confidence: 99%